2014
DOI: 10.1021/jp509158p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Oxidation of Iodide Ion by Persulfate Ion in the Critical Water/Bis(2-ethylhexyl) Sodium Sulfosuccinate/n-Decane Microemulsions

Abstract: In this work, we studied the kinetics of the oxidation of iodide ion by persulfate ion in the critical water/bis(2-ethylhexyl) sodium sulfosuccinate (AOT)/n-decane microemulsions with the molar ratios of water to AOT being 35.0 and 40.8 via the microcalorimetry at various temperatures. It was found that the Arrhenius equation was valid for correlating experimental measurements in the noncritical region, but the slowing down effect existed significantly in the near critical region. We determined the values of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There have been a number of measurements of the rate of reaction near a critical point of solution. The experimental data for the rate constant in the forward direction, k f , have been found to be consistent with the Arrhenius equation , where A f is a constant pre-exponential factor, and is the apparent activation energy. Except for a few cases where no effect could be detected, ,,,, E f has been observed to increase markedly with temperature in the critical region.…”
Section: Introductionmentioning
confidence: 87%
“…There have been a number of measurements of the rate of reaction near a critical point of solution. The experimental data for the rate constant in the forward direction, k f , have been found to be consistent with the Arrhenius equation , where A f is a constant pre-exponential factor, and is the apparent activation energy. Except for a few cases where no effect could be detected, ,,,, E f has been observed to increase markedly with temperature in the critical region.…”
Section: Introductionmentioning
confidence: 87%
“…The value of ΔΑ is independent on the influence of the absorption and light scatting of cobalt-iron PBAs when the absorbance due to the absorption and scattering of PBAs at each of the three wavelengths is linear with the wavelength. [17][18][19][20][21][22] Thus proper choices of the setting absorption wavelengths are crucial, which are required to ensure that the absorbance of cobalt-iron PBAs due to the absorption and scattering in the wavelength range between λ 1 and λ 3 is linear with the wavelength and the values of ΔΑ for K 3 Fe(CN) 6 are sufficiently large. The values of λ 1 and λ 3 were carefully selected to be 410 nm and 440 nm respectively in our study.…”
Section: Three Wavelength Spectrophotometry Measurementsmentioning
confidence: 99%
“…Chow et al [5] reported spherical cobalt-iron PBAs nanoparticles in water-in-oil (w/o) microemulsions containing nonionic surfactants. Vaucher et al [6] obtained cobalt hexacyanoferrate nanoparticles which are well-defined and uniform in size within the range of (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) nm in microemulsion containing anionic surfactant sodium bis(2-ethylhexy) sulfosuccinate (aerosol OT or AOT). Zhao and co-worker synthesized nanoscale cobalt-iron PBAs with shapes of hollow, cube, and sphere in w/o microemulsions containing nonionic surfactant polyoxyethylen tertocthlphenyl ether (Triton X-100) and cationic surfactant cetyltrimethyl ammonium bromide (CTAB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of the SN1 hydrolysis reaction of 2‐chloro‐2‐methylbutane in isobutyric acid/water and of 2‐bromo‐2‐methylpropane in triethylamine/water reduced when the temperature was higher than the critical temperature but accelerated in the temperature region below the critical temperature . Recently, Shen et al . studied the kinetics of a first or pseudo–first‐order reversible reaction in both directions in critical binary or pseudobinary solutions and suggested that the critical slowing down effect of the reaction may be explained by dynamic and thermodynamic anomalies.…”
Section: Introductionmentioning
confidence: 99%